Practical techniques for high-precision measurements on near-term quantum hardware and applications in molecular energy estimation - Keijo Korhonen; Hetta Vappula; Adam Glos; Marco Cattaneo; Zoltán Zimborás; Elsi-Mari Borrelli; Matteo A. C. Rossi; Guillermo García-Pérez; Daniel Cavalcanti (npj Quantum Information)
Abstract Achieving high-precision measurements on near-term quantum devices is critical for advancing quantum computing applications. Quantum computers suffer from high readout errors, making quantum simulations with high accuracy requirements particularly challenging. This paper implements practical techniques to reach accuracies essential for quantum chemistry by addressing key overheads and noise sources. Specifically, we leverage locally biased random measurements for reducing shot overhead, repeated settings with parallel quantum detector tomography for reducing circuit overhead and mitigating readout errors, and blended scheduling for mitigating time-dependent noise. We demonstrate these techniques via molecular energy estimation of the BODIPY molecule on a Hartree-Fock state on an IBM Eagle r3, obtaining a reduction in measurement errors by an order of magnitude from 1-5% to 0.16%. These strategies pave the way for more reliable quantum computations, particularly for applications requiring precise molecular energy calculations.